PROGRAM TELEVISI BROWNIES DALAM TINJAUAN ETIKA DAN HUKUM MEDIA PENYIARAN - Aziza, Reyhan Yozaf; Haq, Hatta Luqmanul; Fauzia, Gefira Afra; Junaedi, Fajar (Universitas Muhammadiyah Jakarta, 2024)
This research aims to review the ethical and legal aspects of broadcast media in the talk show program “Brownies” on Trans TV. The research method used is descriptive qualitative. Data was obtained through observation of television programs based on the Broadcasting Code of Conduct and Broadcast Program Standards (P3SPS). The results showed that the violation of the R-classified program contained scenes that were not in accordance with the classification provisions. This has an impact on audience to do or justify inappropriate behavior for audience who lack education.